2020
DOI: 10.1108/medar-05-2019-0499
|View full text |Cite
|
Sign up to set email alerts
|

Leadership-in-teams, ready, willing and able: perspectives of international accounting students

Abstract: Purpose The purpose of this study is to explore the reasons why international accounting students in higher education in Australia do not accept leadership roles in academic teams, considering the importance employers attach to leadership and teamwork graduate attributes. Design/methodology/approach Adopting the Keating et al. (2014) ready, willing and able (RWA) leadership framework, this qualitative study uses a narrative textual approach to analyse the data from responses to open-ended questions recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Skill refers to a set of proficiency that a person can acquire and maintain through constant practice and training (Yau and Sculli, 1990). A few studies have empirically identified the skills that are considered important for accountants’ professional careers and the extent to which accounting education programmes have contributed to developing these skills (De Lange et al , 2006; Kavanagh and Drennan, 2008; Jackling and De Lange, 2009; O’Connell et al , 2015; Samkin and Stainbank, 2016; Chaplin, 2017; Smith et al , 2018; Miller, 2020; Oosthuizen et al , 2021; Phan et al , 2021). De Lange et al (2006), for example, indicate that graduates consider communication skills, problem-solving and analytical skills and decision-making skills to be some of the most important generic skills for their career success.…”
Section: Relevant Literature and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Skill refers to a set of proficiency that a person can acquire and maintain through constant practice and training (Yau and Sculli, 1990). A few studies have empirically identified the skills that are considered important for accountants’ professional careers and the extent to which accounting education programmes have contributed to developing these skills (De Lange et al , 2006; Kavanagh and Drennan, 2008; Jackling and De Lange, 2009; O’Connell et al , 2015; Samkin and Stainbank, 2016; Chaplin, 2017; Smith et al , 2018; Miller, 2020; Oosthuizen et al , 2021; Phan et al , 2021). De Lange et al (2006), for example, indicate that graduates consider communication skills, problem-solving and analytical skills and decision-making skills to be some of the most important generic skills for their career success.…”
Section: Relevant Literature and Research Questionsmentioning
confidence: 99%
“…Professional accounting bodies have called for a change in the way accountants are educated indicating that more emphasis needs to be given in the accounting curriculum to develop the relevant professional skills (O’Connell et al , 2015; Samkin and Stainbank, 2016). Oosthuizen et al (2021) also indicate that accounting educators need to develop leadership qualities in cohorts of accounting students so that they are being “ready” to adopt leadership roles. Their results show that international accounting students are not “willing” to adopt leadership roles.…”
Section: Relevant Literature and Research Questionsmentioning
confidence: 99%
“…Universities that failed to provide qualified and competent graduates will not achieve a competitive advantage, compared to those universities that can meet the needs of stakeholders (Oosthuizen et al, 2021). While business environment has changed over time and it affects the way business organizations are managed (Nudurupati et al, 2021), the challenge of a business administration curriculum is how to justify which attributes are most important to business administration graduates at the present time (Brauer, 2021).…”
Section: Introductionmentioning
confidence: 99%